Rodzina jako kontekst edukacji dziecka - Rostańska, Eugenia (Studia Edukacyjne, 2025)
The family participates in situations and events that involve the learning child. The course of the child’s school education impacts family everyday life in terms of time management, daily organization, experienced emotions, and, most importantly, communication between adults and the child.